2011
DOI: 10.1002/aic.12297
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cam geometry and operating conditions on chaotic mixing of viscous fluids in a twin cam mixer

Abstract: in Wiley Online Library (wileyonlinelibrary.com).Smooth particle hydrodynamica (SPH) simulations were used to better understand the mixing performance of a class of two-dimensional Twin Cam mixers. The chaotic manifolds of the flow are used to describe the mixing and to identify isolated regions. For an equilateral triangle cam geometry, a figure-eight manifold structure traps a layer of fluid against the cam boundaries. Changes in the differential rotation and phase offsets between the cams results in modest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…[11][12][13][14] Stretching and folding of fluid elements were shown to play a crucial role, increasing the interface area between the two fluids and the concentration gradients, thereby intensifying the mixing process. [15][16][17][18][19][20] In the field of dense granular flows where grains tend to transiently rotate in rotational islands, the advection-diffusion coupling leads to a significant transfer enhancement. 1 However, the link between typical rotational vortex characteristics and the degree of transfer enhancement has not yet been clearly quantified.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Stretching and folding of fluid elements were shown to play a crucial role, increasing the interface area between the two fluids and the concentration gradients, thereby intensifying the mixing process. [15][16][17][18][19][20] In the field of dense granular flows where grains tend to transiently rotate in rotational islands, the advection-diffusion coupling leads to a significant transfer enhancement. 1 However, the link between typical rotational vortex characteristics and the degree of transfer enhancement has not yet been clearly quantified.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, many kinks appear in the CRS, implying the perfect folding action. It is known that the rate of fluid transport across the tangle of a manifold pair is proportional to the area of the lobes [27]. The kink structures in the CRS benefit from increasing the area of lobes, which is important to improve the fluid transport on both sides of the tangles.…”
Section: Resultsmentioning
confidence: 99%
“…The ridges of the finite-time Lyapunov exponent (FTLE) present the most stretching and repelling structures, which are called LCS (It is noted that several studies reported that the ridges of the FTLEs are not LCSs, as they have nonzero flux across them [25]). Many researchers used the FTLE and LCS to study fluid mixing and the transport process in internal mixers [26,27,28,29] and identify the vortex pinch-off [30]. Santitissadeekorn et al [26] used the LCS to investigate the transport behavior and mixing process in a batch mixer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, technical applications of various impeller types are discussed [3][4][5][6][7][8]. Highly viscous fluids are normally mixed by screw or helical ribbon impellers, which have relatively large convective heat transfer coefficients [6][7][8][9][10]. Installation of an electrical heating element inside an impeller blade [11] extends the overall role of the blade from only mechanical to included thermal effects due to heat transfer with the fluid.…”
Section: Introductionmentioning
confidence: 99%